Imiquimod-induced psoriasis in mice depends on the IL-17 signaling of keratinocytes - Moos, Sonja; Mohebiany, Alma N.; Waisman, Ari; Kurschus, Florian (The journal of investigative dermatology, 2019)
The pathology of psoriasis strongly depends on IL-17A. Monoclonal antibodies blocking either the cytokine or its receptor are among the most efficient treatments for psoriatic patients. Keratinocytes can be activated upon exposure to IL-17A and tumor necrosis factor-α and secrete secondary cytokines and chemokines in the inflamed skin. In psoriasis and its imiquimod-induced mouse model, a strong skin infiltration of neutrophils and inflammatory monocytes can be observed. However, to date, it is not clear how exactly those cellular populations are attracted to the skin and how they contribute to the pathogenesis of the disease. To define the crucial cell type responding to IL-17 and initiating the downstream pathology in psoriasis-like dermatitis, we used mice specifically lacking the IL-17 receptor (IL-17RA) in different cell types. Deletion of IL-17RA in T cells or myeloid had no impact on disease development. Only deletion of this receptor in keratinocytes reflected the full-body deletion of IL-17RA, resulting in strongly reduced dermatitis development. Imiquimod treatment of those IL-17 signaling-deficient mice maintained high monocytic infiltration but failed to attract neutrophils into the skin. We conclude that keratinocytes are a critical cellular target for IL-17A-mediated neutrophil attraction and psoriasis development.